Relationship between impact characteristics and launch direction in softball hitting: A study involving elite players - Kidokoro, S.; Morishita, Y. (PLOS ONE, 2021)
In the game of softball, the batter should possess the necessary skills to hit the ball toward various directions with high initial speed. However, because various factors influence each other, there are limitations to the range that can be controlled by the batter`s skill. This study was aimed at extracting the impact characteristics associated with the launch speed/direction and batted ball spin and clarifying the important skills required to improve the batter`s hitting performance. In our experiments, 20 female softball players, who are members of the Japan women`s national softball team, hit balls launched from a pitching machine. The movements of the ball and bat before, during, or after the impact were recorded using a motion capture system. Stepwise multiple regression analysis was performed to extract factors relating the side spin rate. The undercut angle (elevation angle between the bat`s trajectory and the common normal between the ball and bat: DeltaR2 = 0.560) and the horizontal bat angle (azimuth of bat`s long axis at ball impact: DeltaR2 = 0.299) were strongly associated with the side spin rate (total R2 = 0.893, p < 0.001). The undercut angle in opposite-field hitting was significantly larger than that in pull-side hitting (p < 0.001). The side spin rate was associated with the undercut angle because the bat`s distal (barrel) side inclined downward (-29.6 ± 8.7°) at impact. The ball exit velocity was higher when it was hit at a smaller undercut angle (R2 = 0.523, p < 0.001). Therefore, it is deemed desirable to focus on maximizing the ball exit velocity rather than ball spin because the ball-bat impact characteristics vary inevitably depending on the launch direction. Meanwhile, the use of the ball delivery machine and the slower pitched ball are the limiting factors in the generalization of the findings.